Introduction to Issue Five - Patrick Nunnally, Editor (Open Rivers, 2017)

(untitled)
When I got fully engaged with Mississippi River work, in the mid-90s, there was a lot of talk about public-private partnerships. That has ebbed and flowed and morphed over the years, but the idea of partnership has remained. Pretty much anyone in any sector—public, nonprofit, or corporate—understands that work beyond a small one-time project rarely happens through just one entity.